(untitled) (Fiep Bulletin - online, 2011)
Data from the literature tend to show a great relationship between the development of mental functions and motor performance in various sports. Therefore, the development of new methods and tools of analysis appears to facilitate the search and drive new lines of work. In the case of the categories of basic or beginners, there is a constant demand by athletes smarter tactically or know "read" the game quickly and effectively. Metacognition becomes essential for this purpose as it covers the cognitive processes of higher order, or more precisely the "thinking about thinking." In the literature, we observed that the growing interest in metacognitive phenomenon contrasts with the difficulty of measuring it, and that the search for an instrument to respect the concept of metacognition is necessary. To this end, the sheet Note Metacognitive Knowledge (ALBINO, 2003) was initially reviewed. This initial analysis thus resulted in a version called Questionnaire Metacognitive Self-Efficacy for Beginners athletes in team sport (QAEMA -IMC). In a pilot study, this version was administered to athletes (n = 120) of both sexes, practice sports conferences, at the School of Maranhão - JEM’S 2009. The difficulties reported by participants led to the development of a second version of the original questionnaire. Finally, looking ahead to the reproducibility of the instrument in relation to content validity, it passed the examination of three experts. Reproducibility was asserted by the high percentage of registered agreements, most of the above limits of 80%.